Is Group Guidance with Problem Solving Technique Effective in Enhancing Students’ Learning Independence? - Herlambang, Refri Sunu; Agungbudiprabowo, Agungbudiprabowo; Nugraha, Ariadi; Mukti, Taquddin Abd; Luhanarky, Ayu (Universitas Ahmad Dahlan, 2024)
This study aims to know the effectiveness of group guidance using problem-solving technique to increase students' learning independence in junior high schools. The type of research conducted in this study is an experiment with a pre-experimental research design, utilizing the one-group pretest-posttest design model. The sample was determined using simple random sampling, consisting of a total of ten students. The data collection instrument used was a learning independence scale. Data analysis was performed using the paired sample test. The results of this study indicate that group guidance using problem-solving technique is effective in enhancing students’ learning independence. The findings of this research can serve as a technical solution for guidance and counseling services for guidance and counseling teachers in their efforts to increase students’ learning independence in junior high schools.